Effect of summer fire on cursorial spider (Aranei) and beetle (Coleoptera) assemblages in meadow steppes of Central European Russia - Polchaninova, Nina; Tsurikov, Mikhail; Atemasov, Andrey (Hacquetia, 2016)
Fire is an important structuring force for grassland ecosystems. Despite increased incidents of fire in European steppes, their impact on arthropod communities is still poorly studied. We assessed short-term changes in cursorial beetle and spider assemblages after a summer fire in the meadow steppe in Central European Russia. The responses of spider and beetle assemblages to the fire event were different. In the first post-fire year, the same beetle species dominated burnt and unburnt plots, the alpha-diversity of beetle assemblages was similar, and there were no pronounced changes in the proportions of trophic groups. Beetle species richness and activity density increased in the second post-fire year, while that of the spiders decreased. The spider alpha-diversity was lowest in the first postfire year, and the main dominants were pioneer species. In the second year, the differences in spider species composition and activity density diminished. The main conclusion of our study is that the large-scale intensive summer fire caused no profound changes in cursorial beetle and spider assemblages of this steppe plot. Mitigation of the fire effect is explained by the small plot area, its location at the edge of the fire site and the presence of adjacent undisturbed habitats with herbaceous vegetation.